Total Quality Management Practices and Microfinance Institutions Performance in Yemen: The Resource Based View Theory Perspective - Min, Khor Wei; Homaid, Abdo Ali; Minai, Mohd Sobri; Zain, Ali Yusob Md (International Review of Management and Marketing, 2016)
The total quality management (TQM) practices in most of the organizations have proven to be the key strategic approach to ensure the peak performance of the firms. In the microfinance institutional contexts, the contribution of TQM is undeniably importance. From a study that has been conducted in Yemen, 125 usable questionnaires were collected using a self-administered technique and analyzed from the branch managers of the MFIs operating in this country. It was done in 2014 at the early stage of the political crisis in the country where most financial institutions were not functioning at the optimum level. The analysis is based on the partial least squares (PLS) approach, evaluating the research framework, the measurement model and the structural model. The results show that TQM has a significant effect on the MFIs performance and support the resource-based view theory, the underlying theory for the research that views the organizational resources as a source of sustainable competitive advantage. The findings provide useful insights into the practices and the contribution of the TQM to the microfinance institutions and could be the benchmark for the practices in the middle-east countries as well as for the country where the political stability is not there. Keywords: Total Quality Management, Microfinance Institutions Performance, RBV theory JEL Classifications: L5, G21